PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SMP NEGERI 2 NGRAMPAL SRAGEN - -, Samto -; -, Mulyanto - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT The results of the research (Test F) are known the value of F = 125,473 significance 0,000 <0,05. Soit can be concluded jointly variables Leadership, Job Satisfaction and Organizational Commitment has positive and significant impact on performance. From t tests concluded that the variables of leadership, Job Satisfaction and Organizational Commitment has positive and significant impact on performance. This can be proved by looking at the significance of each variable <0,05. RÂ² obtained from test results for 0892 or 89.2 %. Which meanc the variability of the dependent variable can be explained by the variability of the indevendent variables not included in the regression models such as motivation, level of education and work environment. Keywords: leadership, job satisfaction, organizational commitment, teacher performance.